Type of settlement as a determinant of marital and reproductive behaviour of young people - Pesic Jenackovic, Dragana (Sociološki pregled, 2021)
The paper explores the importance of the type of settlement for marital and reproductive behaviour of young people. More specifically, it examines the differences in the evaluation and practice of certain forms of marital and reproductive behaviour between young people living in different types of settlements. The data were collected with the aid of quantitative techniques like surveys and scaling. The research was conducted in the region of Southern and Eastern Serbia. The quota sample consisted of the total of 500 respondents, aged from 15 to 35 years. The results of the research show that the type of settlement is an important determinant, but more for the purpose of evaluation than for practising certain models of marital and reproductive behaviour of young people. Young people living in villages are more loyal to the traditional values in terms of marriage and parenthood, while young people living in the city tend to embrace modern values. However, practice shows that rural youth, besides maintaining traditional patterns of behaviour, also manifests certain deviations from them (like postponement of marriage and parenthood, reduced reproductive norms, cohabitation and out-of-wedlock parenting).